PERANCANGAN STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI PANGADARAN, JAWA BARAT - Bernard Hasibuan; Lisa Ratnasari; Ninin Gusdini (Universitas Muhammadiyah Surakarta, 2021)
Pangandaran is one of the famous tourist destinations because it is complete with several attractions such as natural attractions, cultural tourism, artificial tourism and conservation. To develop a very potential destination, a comprehensive development strategy is needed. The methods used in this study are SWOC and AHP, the first of which is the exploration of SWOC to identify factors of strengths, weaknesses, opportunities and challenges. The second stage is to sabotage the proposed strategy obtained with AHP. Hasil this research there are4 proposed strategies, namely optimizingsocial media for promotion (weight 0.419), involving Stakeholders to participate in the development of Pangandaran (weight 0,300), making tour packages that include existing attractions(Homestay, protected forest) (weight 0,168), and building a sustainable Pangandaran system. integrated g (weight 0.113). Pangandaran development must follow existing trends with social media technology that can expand marketing reach.